Religious education and containment of radical elements: The case of pondok schools in Malaysia - Fathil, Fauziah; Oktasari, Wiwin (Fakulti Tamadun Islam, Universiti Teknologi Malaysia, 2017)
Islam and militant activities are indeed two ill-assorted and incompatible elements. While the former enjoins harmony and peace, the latter is essentially destructive in nature with no regard for either lives or properties The occurrence of many events which involved radical or militant elements today caused a growing concern that education too, might have been used by some irresponsible groups to spread their radical ideas in order to recruit followers or supporters where young minds are taught to hate people of other beliefs or ideologies and to commit destructive acts. In Malaysia, while phenomenon involving radical ideas is generally under control, still there have been some allegations that a certain style of education particularly of pondok system, being involved in militant-related activities. Based on qualitative approach or content-analysis, this paper attempts to seek out reasons for such allegations, highlighting certain issues and prior events that happened in the country which might have contributed to these contentions. The paper also provides possible means and ways, in view of the existing scenario in Malaysia, in making sure that religious education in the country remains free from the unwanted radical elements or ideas.